1999
DOI: 10.1097/00004032-199903000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Experiences With High Dose Radiopeptide Therapy

Abstract: One of the new, promising areas of nuclear medicine involves radiolabeled low-molecular-weight peptides for the diagnosis and management of cancer. Somatostatin analogous peptides bind to membrane receptors on tumors with high specificity. These analogues, when radiolabeled with 123I, 131I, 99mTc, or (111)In, allow for external scintigraphic imaging or radioguided surgical resection of tumors. Somatostatin analogues with high tumor binding affinity have also been used for high-dose radiotherapy at the Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Based on these observations, it appears that similar receptors and post-receptor signal transduction pathways are responsible for somatostatin's ability to inhibit peptide release, tumour growth, and angiogenesis (Bhatena et al, 1981;Thompson et al, 1986;Woltering et al, 1986;Wynick and Bloom, 1991). The widespread use of radiolabelled somatostatin analogues in patients with neuroendocrine tumours has demonstrated that these sst 2-containing tumours avidly bind radiolabelled sst 2-preferring somatostatin analogues such as tyr 3 -octreotide, lanreotide, and pentetreotide (Schirmer et al, 1993;Woltering et al, 1994;Martinez et al, 1995;Woltering et al, 1995;McCarthy et al, 1998;Cuntz et al, 1999;Espenan et al, 1999). Inevitably, as larger numbers of tumour-bearing patients have been scanned with these radiolabelled analogues, tissues and organs subjected to nontumour disease processes have been shown to bind these radioligands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on these observations, it appears that similar receptors and post-receptor signal transduction pathways are responsible for somatostatin's ability to inhibit peptide release, tumour growth, and angiogenesis (Bhatena et al, 1981;Thompson et al, 1986;Woltering et al, 1986;Wynick and Bloom, 1991). The widespread use of radiolabelled somatostatin analogues in patients with neuroendocrine tumours has demonstrated that these sst 2-containing tumours avidly bind radiolabelled sst 2-preferring somatostatin analogues such as tyr 3 -octreotide, lanreotide, and pentetreotide (Schirmer et al, 1993;Woltering et al, 1994;Martinez et al, 1995;Woltering et al, 1995;McCarthy et al, 1998;Cuntz et al, 1999;Espenan et al, 1999). Inevitably, as larger numbers of tumour-bearing patients have been scanned with these radiolabelled analogues, tissues and organs subjected to nontumour disease processes have been shown to bind these radioligands.…”
Section: Discussionmentioning
confidence: 99%
“…While the heterogeneous expression of sst 2 on tumour cells is ubiquitous, it appears that all proliferative neovessels homogeneously express this receptor. This difference in receptor expression may permit the use of low energy radioisotopes for therapy (McCarthy et al, 1998;Espenan et al, 1999). Sst 2-targeted applications may include intraoperative gamma localization of occult primary tumours, and intraoperative gamma detection of microscopically positive primary tumour resection margins (Schirmer et al, 1993;Woltering et al, 1994;Martinez et al, 1995;Cuntz et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonged (24 -48 h) exposure of somatostatin receptorexpressing cells to iodine or indium-labeled somatostatin analogs leads to progressive increases in whole cell binding, internalization, and receptor-dependent nuclear transport of the radioligand [12]. Exposure of somatostatin receptor-expressing cells to Augeremitting radiolabeled somatostatin analogs also induces dose-dependent/receptor-dependent cytotoxicity both in vitro and in vivo [13][14][15][16]. These observations have led us to investigate the relative contribution of radioligand concentration and radioligand exposure time on binding, internalization, and cytotoxicity in somatostatin receptor-expressing cells.…”
Section: Introductionmentioning
confidence: 99%